Growth behavior and soil plant water relations as influenced by irrigation levels in barley genotypes - Verma, R. K.; Kumar, A.; Ghasal, P.C.; Thakaral, S.K. (Annals of Agricultural Research, 2018)
A field experiment was conducted during winter (rabi) season of 2011-2012 to study the effect ofirrigation on growth and soil plant water relation of barley. The results revealed that irrigation andgenotypes significantly influenced the phenology, growth of barley and soil plant water relationsviz., leaf water potential, relative water content and soil moisture content. The growth parameterssuch as plant height, number of tillers and dry matter accumulation increased with the increase inirrigation frequency. In plant water relations, leaf water potential and relative water content washigher under two irrigations compared to one irrigation. Among the tested genotypes, plant heightwas highest in genotype BH 09-21(84 cm). Number of tillers were recorded highest in genotypes BH08-36 (113) followed by BH 08-16 (107). Similarly, maximum leaf area index was recorded in BH 902(5.21) as compared to other remaining genotypes. Interaction effect was also observed betweenirrigation and genotypes with respect to leaf water potential. At one irrigation, genotype BH 09-44(-1.74 MPa) and BH 08-36 (-2.06 MPa) showed highest and lowest leaf water potential, respectively.Whereas genotype BH 09-05 (-1.60 MPa) showed the highest leaf water potential at two irrigationlevels. Genotype BH 05-20 (82.96%) and BH 08-16 (87.03%) registered maximum relative watercontent at one and tow irrigations, respectively. The interaction between irrigation and barleygenotypes was also significant for most of the characters indicating differential behavior of barleygenotypes to two irrigation levels.